Adaptive response of Rhodococcus opacus PWD4 to salt and phenolic stress on the level of mycolic acids - de Carvalho, Carla C. C. R. (AMB Express, 2016)
Mycolata form a group of Gram-positive bacteria with unique cell envelope structures that are known for their high tolerance against antibiotics and both aromatic and aliphatic hydrocarbons. An important part of the unique surface structure of the mycolata is the presence of long chain α-alkyl-β-hydroxy fatty acids, the mycolic acids. In order to investigate the adaptive changes in the mycolic acid composition, we investigated the composition of mycolic acids during the response both to osmotic stress caused by NaCl and to 4-chlorophenol in Rhodococcus opacus PWD4. This bacterium was chosen as it is known to adapt to different kinds of stresses. In addition, it is a potential biocatalyst in bioremediation as well as for biotechnological applications. In the present study, cells of R. opacus PWD4, grown in liquid cultures, responded to toxic concentrations of NaCl by increasing the ratio between mycolic acids and membrane phospholipid fatty acids (MA/PLFA-ratio). Cells reacted to both NaCl and 4-chlorophenol by decreasing both the average chain length and the unsaturation index of their mycolic acids. These changes in mycolic acid composition correlated with increases in cell surface hydrophobicity and saturation of membrane fatty acids, demonstrating the relation between mycolic acid and phospholipid synthesis and their contribution to cell surface properties of R. opacus PWD4.